Prevalence of Malnutrition in a Rural Residential Sanskrit School in Baglung, Nepal - Bhawana Amatya; Nitesh Shrestha (Journal of Nepal Medical Association, 2017)
Introduction: Under-nutrition is a condition in which there is inadequate consumption, poor absorption or excessive loss of nutrients. Nepal still faces high chronic as well as acute under‐nutrition in children. The following study was conducted a Sanskrit school in rural Baglung to find the prevalence of malnutrition among the children which could reflect the nutritional status of the community.